2017
DOI: 10.1093/mnras/stx055
|View full text |Cite
|
Sign up to set email alerts
|

BAT AGN Spectroscopic Survey - IV: Near-Infrared Coronal Lines, Hidden Broad Lines, and Correlation with Hard X-ray Emission

Abstract: We provide a comprehensive census of the near-Infrared (NIR, 0.8-2.4 µm) spectroscopic properties of 102 nearby (z < 0.075) active galactic nuclei (AGN), selected in the hard X-ray band (14-195 keV) from the Swift-Burst Alert Telescope (BAT) survey. With the launch of the James Webb Space Telescope this regime is of increasing importance for dusty and obscured AGN surveys. We measure black hole masses in 68% (69/102) of the sample using broad emission lines (34/102) and/or the velocity dispersion of the Ca II … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
98
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(108 citation statements)
references
References 80 publications
7
98
2
1
Order By: Relevance
“…Koss et al (2017) presented an overview of the optical spectroscopic data. Additional extended multi-wavelength campaigns from near-IR (NIR) to soft X-ray wavelengths (Berney et al 2015;Lamperti et al 2017;Oh et al 2017;Ricci et al 2017b;Trakhtenbrot et al 2017;Ricci et al 2017a;Oh et al 2018;Powell et al 2018;Ricci et al 2018;Shimizu et al 2018) have allowed us to further characterize the BASS sample, studying for example the connection between X-ray and optical obscuration, NIR lines, X-ray photon index, absorption and coronal properties.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Koss et al (2017) presented an overview of the optical spectroscopic data. Additional extended multi-wavelength campaigns from near-IR (NIR) to soft X-ray wavelengths (Berney et al 2015;Lamperti et al 2017;Oh et al 2017;Ricci et al 2017b;Trakhtenbrot et al 2017;Ricci et al 2017a;Oh et al 2018;Powell et al 2018;Ricci et al 2018;Shimizu et al 2018) have allowed us to further characterize the BASS sample, studying for example the connection between X-ray and optical obscuration, NIR lines, X-ray photon index, absorption and coronal properties.…”
Section: Datamentioning
confidence: 99%
“…Catalog (MIUSCAT) library of stellar spectra (Vazdekis et al 2012). The galaxy continuum and stellar absorption features were removed, as explained in Koss et al (2017) and in Lamperti et al (2017). Our fi- nal sample is comprised of 210 type 2 AGN, and 92 type 1.9 AGN with a satisfactory host continuum subtraction.…”
Section: Continuum Fitting (4400-5500å)mentioning
confidence: 99%
“…A large number of works have already been carried out studying pointed X-ray observations (e.g., Winter et al 2009b;Ricci et al 2010;Tazaki et al 2011Tazaki et al , 2013Kawamuro et al 2016b;Tanimoto et al 2016;Marchesi et al 2017;Oda et al 2017) and the multiwavelength properties of Swift/BAT AGNs. This includes radio (e.g., Burlon et al 2013;Wong et al 2016), far-IR (e.g., Meléndez et al 2014;Mushotzky et al 2014;Shimizu et al 2015Shimizu et al , 2016, mid-IR (e.g., Meléndez et al 2008;Weaver et al 2010;Ichikawa et al 2012Ichikawa et al , 2017, near-IR (e.g., Mushotzky et al 2008;Lamperti et al 2017;Onori et al 2017aOnori et al , 2017bRicci et al 2017d), optical (e.g., Vasudevan et al 2009;Koss et al 2010;Winter et al 2010;Ueda et al 2015), and γ-ray (e.g., Sambruna et al 2010;Teng et al 2011) studies, as well as works focused on the host galaxy properties (e.g., Koss et al 2011b), on variability (e.g., Shimizu & Mushotzky 2013;Soldi et al 2014), and on peculiar sources (e.g., Koss et al 2012;Hogg et al 2012;Smith et al 2014;Schawinski et al 2015). Moreover, NuSTAR has been observing Swift/BAT AGNs since its launch in the framework of a legacy survey (M. …”
Section: Introductionmentioning
confidence: 99%
“…A large effort has been made to collect optical spectroscopy for most of the sources reported in the 70-month Swift/BAT catalog, which allowed us to infer black hole masses for both obscured and unobscured objects . The first results of the Swift/BAT AGN Spectroscopical Survey (BASS) include the study of the CT AGNs detected by BAT (Ricci et al 2015; see also Koss et al 2016a;Akylas et al 2016), the analysis of the correlation between high-ionization optical emission lines and AGN X-ray emission , the study of the relationship between optical narrow emission lines and the physical parameters of the accreting SMBH (Oh et al 2017), a near-IR spectroscopic study (Lamperti et al 2017), and the analysis of the relationship between the X-ray photon index and the mass-normalized accretion rate . The detailed multiwavelength analysis of a large sample of local AGNs 24 will be a very important benchmark for studies of AGNs at higher redshifts, where the typical fluxes are significantly lower.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 5 years a massive effort has been made in investigating complete census of black hole masses (M BH ) and accretion rates normalized by M BH (λ Edd , λ Edd ≡ L bol /L Edd , where L Edd ≡ 1.3×10 38 (M BH /M ⊙ )) of X-ray selected AGN. Based on the 70-month catalog of Swift -BAT (Baumgartner et al 2013), which identified 836 AGN, the BAT AGN Spectroscopic Survey Data Release 1 (BASS-DR1 2 , Koss et al 2017;Lamperti et al 2017;Ricci et al 2017) published M BH , λ Edd , narrow/broad emission-line strength, emissionline diagnostics, stellar velocity dispersion, and X-ray spectral properties for 642 AGN ( z ∼ 0.05) using various public surveys (the Sloan Digital Sky Survey and the 6dF Galaxy Survey; Abazajian et al 2009;Jones et al 2009;Alam et al 2015) and dedicated follow-up optical/near-infrared spectroscopic observations.…”
Section: Introductionmentioning
confidence: 99%